Comparison of some kinematic variables of the triple jump between the two world championships (IAAF) (2017) and (2018) - Ahmed Sabea Atiya; Yasir Najah Hussein; Hasnaa Sattar Jabbar; Firas Mutasher Abdulreda; Ahmed Thamir Mohsin; Huda Hameed Abdulhuseen; Laith Fares Jameel; Hisham Hamdan Abbas (Eximia, 2024)
The study aimed to compare some of the kinematic variables and achievement between the competitions (2017) and (2018) in triple jump to find the percentages of the teams, which may indicate the reasons for the different level of the two championships. Statistical difference, although we may not find these differences in all variables, especially achievement, but at such global levels the differences of the few numerical parts make a difference in global achievements, numbers and medals. The researcher adopted the descriptive approach using the method of comparisons to extract the results of the study, and the research community consisted of (27) jumpers (12) competitors in the (2017) championship and (15) competitors in the (2018) championship, and the statistical bag (SPSS) was used to extract: (Mean ), (Std.Divition), (Independent-Sample.T.Test). This study found that the Hop angle and Length of speed Jump is the most influential interval in the best achievement. The researcher recommends following up on such international reports and comparisons because they may give solutions and orientation in training for the most influential factors at different levels of achievement.